Anais da VI Jornada Científica da Faculdade Sul Fluminense- Resumos Expandidos - Barbosa, Marcus Vinícius; Triani, Felipe da Silva (Revista Valore, 2020)
Anais da VI Jornada Científica da Faculdade Sul Fluminense- Resumos Expandidos